(3JMUjd dHGH GdMceIs - (3HgefjGQ Hf GdeQRHGf GdGPQHjLGf, CHh GdMSf,J (B458 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3GdMeO ddg MeOkG jSJMbg HYdh TCfg hSHhZ GMSGfg aEfi eMUd ai gPg GdQSGdI cJGH GdMceI GdJi jPHgG GdTjN Hf SjfG hjfbSe gPG GdcJGH Edi KdGKI cJH aGdcJGH GdChd ai GdefWb hjTJed Ydi KdGKI ebGdGJ s
(3BNQgG (B:s
(3adGSHjd Edi eYQhaI GMhGdgG HGdHQgGf hgPG GdbOQ ef GdMceI EPG GMce Sgd GdSHjd Edi eG HYOg Ydi GdJObjb hGdJaVjd hGdHSjW hGdJMbjb hfSCd Gddg GdJhajb Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs